(untitled) (Research, Society and Development, 2022)
This study aims to carry out an integrative review on the importance of the insertion of nurses in public schools. This is an integrative review with a descriptive exploratory approach of a qualitative nature between the period from 2013 to 2017, the information was collected in the Virtual Health Library (VHL) where we selected the Latin American and Caribbean Literature on Health Sciences databases. Health (LILACS) and Medical Literature Analysis and Retrievel System Online (MEDLINE). The study was able to highlight the importance of the insertion of nurses in public schools. The work of this professional aims to promote students’ self-care, in this field the nurse is seen as an educator and the school is the ideal setting to carry out health education activities. Nurses work directly in the prevention and promotion of school health for children and adolescents through health education, however, strengthening the link between school and health is essential for maintaining quality of life.